Epiphenomenalism looming large: \"mental quausation\" and the threat of exclusion - Lima, Victor Nicolau Sholl de Freitas (2022)
This masters\' dissertation is about mental causation, in specific, about what is called the causal exclusion problem. Made famous by Jaegwon Kim, the problem consists in an apparent tension between certain premises that are generally assumed to be plausible, but that could not all be true at the same time. In broad terms, the problem can be formulated like this: since there is always a physical cause available to explain the occurrence of every physical effect, then, if mental causes are not reducible to physical causes, how can there be mental causes of physical effects without implying that some form of causal overdetermination occurs? Building up on this problem, the causal exclusion argument is an argument that puts the tension on the nonreductionist premise, seeking to conclude that nonreductionist theses about the mind would lead to epiphenomenalism (the thesis that there some mental states that do not cause anything). My dissertations seeks to show that the threat posed by the problem and argument of exclusion is more serious than what is usually assumed in the literature. To accomplish this, I defend that accounts of mental causation that seek to avoid epiphenomenalism must preserve the general notion of \"mental quausation\" defended by Terrence Horgan. This project is divided into three parts: in the first, I introduce some concepts and topics about mental causation more broadly, the problem of exclusion, and the exclusion argument, discussing what would be at stake with them. In the second part, I introduce the notion of \"mental quausation\", defend its importance and discuss some ways to capture its general idea in more precise terms. In the third part, I introduce a new version of the exclusion argument that is wider in scope. I also present and respond to a possible objection to my argument in the form of Menzies & List theory of causation as making a difference. I then generalise the exclusion problem in the form of the Epiphenomenalist Dilemma and the Trilemma of Mental Efficacy, discussing some devastating implications of the result.